Assessment of Knowledge, Attitude and Practices Related to Occupational Hazards among Nurses of Tertiary care Hospitals of Rawalpindi: Occupational Hazards Among Nurses - Shaheen, Dure Yakta; Diba, Farah; Khan, Jawaria; Habib, Muhammad Farrukh; Raisani, Sher Afgan; Bashir, Nazia; Bashir, Rehana; Zulfiqar, Shaista; Kakakhel, Ihtishaam; Javed, Aaliya (Pakistan Journal of Health Sciences, 2023)
Occupational hazards associated with health are present in every occupation, and they are the leading cause of death. In the medical profession, Nurses constitute the largest group of healthcare workers, and experience a higher rate of workplace hazards exposure than other health care workers. Objective: To assess the knowledge, attitude and practices of occupational hazards among nurses in tertiary care hospitals of Rawalpindi. Methods: A sample of 422 nurses having clinical experience of more than one year were recruited through multistage sampling. A modified, validated and pretested questionnaire was administered. Data were coded into SPSS version-23. Mean ± SD were calculated for (numerical) variables. Frequency and percentage were calculated for categorical variable. For the association, p-value <0.05 was considered significant. Results: The results showed respondents with a mean age of 37.63±6.73. Most had high knowledge 370(87.7%) about hazards in Hospitals, with positive attitude 311(73.70%), Only 218(51.7%) comply safety practice whilst those that did not follow 204(48.3 %) generally associate as deficient of essential safety equipment 222(52.6. %). There was no association between knowledge, attitude, and practices. Conclusions: Satisfactory knowledge, positive attitude and poor practices of nurses are key impediments to nurses. Improve the practices and reduce the exposure of occupational hazards